Resilience and Related Factors: A Comparison of Fathers and Mothers of Patients With Cleft Lip and/or Palate in China - Yuan, Lulu; Gao, Yuqin; Pan, Bochen; Wang, Junyan; Wang, Yanjie; Gong, Caixia; Wang, Weiren; Li, Xiaohan (Frontiers in Psychiatry, 2022)
Background: Resilience has become a hot spot in the field of positive psychology to study life-change events. However, there were little information on resilience among the fathers and mothers of patients with cleft lip and/or palate respectively. The present study aimed to explore and compare the level and potential influential factors associated with resilience among fathers/mothers of patients with cleft lip and/or palate in China. Method: A cross-sectional study was carried out between April 2019 and July 2020 among fathers/mothers of patients with cleft lip and/or palate in two cleft lip and/or palate treatment centers in China. Sixty Nine fathers and 179 mothers of patients with cleft lip and/or palate were interviewed with a questionnaire on demographic variables and the Resilience Scale-14 (RS-14), Herth Hope Index (HHI), Multidimensional Scale of Perceived Social Support (MSPSS), Revised Life Orientation Test (LOT-R), Parenting Stress Index-Short Form (PSI-SF) and Coping Health Inventory for Parents (CHIP). T-test/univariate one-way ANOVA, Pearson's r, hierarchical linear regression analysis were conducted to explore the influential factors of resilience. Results: Fathers of patients with cleft lip and/or palate had a higher level of resilience (77.77 ± 14.18) than mothers (74.52 ± 14.33) though without significance. Resilience was positively associated with hope, perceived social support, optimism and coping and negatively correlated with parenting stress both in the fathers and the mothers. Hierarchical linear regression analysis showed that hope (β = 0.400, P < 0.01), coping (β = 0.281, P < 0.05), job status, medical payments (β = −0.240, P < 0.05) were found to be associated with resilience among the fathers of patients with CL/P, and all four variables in the model could explain 42.8% of the variance in resilience; Hope (β = 0.225, P < 0.05), perceived social support (β = 0.194, P < 0.05), the age of patients (β = 0.189, P < 0.05) were found to be associated with resilience among the mothers, and all three variables in the model could explain 27.6% of the variance in resilience. Conclusion: Our study showed that, in China, fathers of patients with cleft lip and/or palate had a higher level of resilience than mothers though without significance. Hope was the only communal variable strongly associated with resilience among both the fathers and the mothers; besides, coping, job status and medical payments were found to be associated with resilience among the fathers; while perceived social support and the age of patients were found to be associated with resilience among the mothers. The results suggest that enhance hope in parents of patients with cleft lip and/or palate might greatly help improve their resilience. Besides, fathers and mothers need specific intervention to prompt their resilience.